Determination of thermal diffusivity by transient analysis of spherically shaped metal specimen - Villanueva, Eliseo P. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2000)
The partial differential equation that governs the conduction of heat is applied to a spherically shaped specimen. The solution to the equation was derived with the assumption that the surface heat resistance is negligible compared with the body heat resistance and that the body does not generate heat. The solution is an equation with time and thermal diffusivity as the independent variables and temperature as the dependent. The equation is to be used for the determination of thermal diffusivity with known values of time and temperature. A computer program was generated for the numerical calculation of the thermal diffusivity and its accuracy was investigated.